Acta Universitatis Wratislaviensis. Prawo. 2018, 325. Studia historycznoprawne - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article is devoted to incest in ancient Greece. In the introduction the author deals with terminological questions, explaining the reasons behind a lack of a general term for incest in the Greek language and how this phenomenon was reflected in Greek literature. Next, he analyses the sources testifying to the existence of a legal ban on incest between direct relatives. He stresses that in Athens it derived from unwritten common law (ágraphos nómos) and was probably never raised to the status of statutory law. In addition, the author analyses sources concerning the legal restrictions placed on sexual intercourse between collateral relatives. The ban on incest applied to siblings, also stepbrothers and stepsisters, who had, depending on the model adopted in a given polis, the same mother (Athens) or the same father (Sparta). The author also examines the question of sexual relations between relatives by affinity, concluding that the Greeks regarded them as adultery. In the last part of his study he explores the sanctions associated with the violation of the incest ban.
Keywords: kazirodztwo; starożytna Grecja; prawo ateńskie